2020
DOI: 10.3390/ijerph17176112
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Predictive Validity of the Burnout Granada Questionnaire in Police Officers

Abstract: Professionals with burnout have negative physical and psychological effects, with adverse consequences in their workplace. Burnout mainly affects assisting professions; amongst them, police work is one of the professions at risk of suffering from this syndrome. The aim of this research is to study the adequacy of the Maslach Burnout Inventory and Granada Burnout Questionnaire instruments to measure burnout in police officers through the study of the reliability and validity (concurrent and predictive) of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, certain positions require working abroad (e.g., embassies) or working away from their units for months due to reasons of national and public security, irrespective of the area they work (Scientific, Information, Immigration and borders, Judiciary and Public safety). Different studies carried out in Spain have shown that police officers are highly likely to suffer from work-related stress due to the tasks of their work [1], such as responding to emergency calls, arresting violators, delivering warrants, mediating conflicts between citizens promptly, which, in turn, harms their physical and psychological wellbeing [2][3][4]. Although previous research has also shown that flexibility-oriented cultures exert their positive effects on employees' job satisfaction (among others) [15], as far as our knowledge reaches, there is an absence of empirical studies focused on how a flexibility-oriented organizational culture can reduce the negative effects of work demands of Spanish police officers, that is to say, facilitate positive outcomes at the employee level.…”
Section: Study Aimsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, certain positions require working abroad (e.g., embassies) or working away from their units for months due to reasons of national and public security, irrespective of the area they work (Scientific, Information, Immigration and borders, Judiciary and Public safety). Different studies carried out in Spain have shown that police officers are highly likely to suffer from work-related stress due to the tasks of their work [1], such as responding to emergency calls, arresting violators, delivering warrants, mediating conflicts between citizens promptly, which, in turn, harms their physical and psychological wellbeing [2][3][4]. Although previous research has also shown that flexibility-oriented cultures exert their positive effects on employees' job satisfaction (among others) [15], as far as our knowledge reaches, there is an absence of empirical studies focused on how a flexibility-oriented organizational culture can reduce the negative effects of work demands of Spanish police officers, that is to say, facilitate positive outcomes at the employee level.…”
Section: Study Aimsmentioning
confidence: 99%
“…To measure work demands, perceived social support, and job control, the Spanish validation [42] of the Job Content Questionnaire (JCQ) [4] was used. This questionnaire comprises three dimensions: psychological demands (six items), job control (seven items), and job support (eight items).…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to obtain evidence of the validity of the Cuestionario Burnout Granada-University Students, in this case, in a sample of nursing students. The CBG-USS is introduced as a university student version of the Cuestionario Burnout Granada (CBG), which has been utilized and validated as a screening tool for burnout syndrome in Nurses and Police Officers [62][63][64]. Since the CBG-USS is a recently created instrument, a reference instrument has been used to demonstrate the correct functioning in the measurement and detection of burnout, in this case, the MBI-SS [19,53], the student version of the MBI [32].…”
Section: Discussionmentioning
confidence: 99%